Literacy is power: structural drivers of child malnutrition in rural Liberia. Issue 2 (1st December 2020) - Kumeh, Odell W; Fallah, Mosoka P; Desai, Ishaan K; Gilbert, Hannah N; Silverstein, Jason B; Beste, Sara; Beste, Jason; Mukherjee, Joia S; Richardson, Eugene T
Abstract : Background: In Liberia, an estimated 32% of children under 5 are stunted. Malnutrition and hunger worsened during the country's civil war and were further exacerbated by the 2014–2016 outbreak of Ebola virus disease. Studies examining adherence to recommended infant and young child feeding practices frequently do so with an emphasis on the knowledge, attitudes and beliefs of mothers and caregivers. Often overlooked are the structural factors that enable or constrain their agency to practise evidence-based recommendations. Methods: Between July and December 2017, we surveyed 100 Liberian mothers to assess the sociodemographic factors associated with the risk of severe acute malnutrition in children in Maryland County, Liberia. We also conducted 50 in-depth interviews at two government health facilities to qualitatively explore mothers' experiences, as well as health workers' understandings of the determinants of malnutrition in the region. We applied logistic regression to analyse quantitative data and inductive content analysis to thematically interpret qualitative data. Results: Mothers were less likely to have a child with severe acute malnutrition if they had an income greater than US50 per month (adjusted OR (aOR)=0.14, p<0.001), were literate (aOR=0.21, p=0.009) or exclusively breast fed during the first 6 months of life (aOR=0.18, p=0.049); they were more likely to have a child with severe acute malnutrition if they were married or in domestic partnerships (aOR=8.41, p<0.001). In-depth interviews elucidated several social, economic and programmatic factors that shaped suboptimal feeding practices, as well as decisions for and against seeking formal care for malnutrition. Discussion: The lived experiences of Liberian mothers and health workers illustrate that child malnutrition is a direct consequence of abject poverty, food insecurity, illiteracy, the precarious nature of formal and informal work, and the lack of robust social protection. Behaviour change and health education interventions that do not seek to alleviate structural barriers to compliance are unlikely to be effective.